Chemometric profile & antimicrobial activities of leaf extract of Calotropis procera and Calotropis gigantea. Issue 16 (18th August 2017) - Pattnaik, Pratap Keshari; Kar, Dattatreya; Chhatoi, Hiranyamayee; Shahbazi, Sajad; Ghosh, Goutam; Kuanar, Ananya
Abstract: Calotropis procera and Calotropis gigantea are medicinal plant having therapeutic value. The leaf extracts of C. procera have been investigated, its pharmacological actions in detail and leaf extracts of C. gigantea were not studied till date. The objective of present work was to find the bioactive constituents present in the ethanolic leaf extract of C. procera and C. gigantea to evaluate their antibacterial and anifungal activities. The major phytochemical groups in C. procera ethanolic leaf extracts were fatty acid ethyl ester (21.36%), palmitic acid ester (10.24%), linoleic acid (7.43%) and amino acid (8.10%) respectively, whereas ethanolic leaf extracts of C. gigantea contain palmitic acid (46.01%), diterpene (26.53%), triterpene (17.39%), linoleic acid (5.13%) as the major phytochemical groups. Ethanol extract of C. procera leaves showed the highest inhibition (11 mm) against Escherichia coli, while ethanolic extract of C. gigantea leaves inhibited Klebsiella (20 mm). These findings will use in new directions in pharmacological investigations. Abstract :